Panel reliability assessment for FPSOs. (1st January 2017) - Chen, Nian-Zhong
Highlights: A methodology is developed for panel reliability assessment for ship-shaped FPSOs. Axial compressive loads and internal and external lateral pressures are taken into account. Variability of corrosion and material properties are considered in panel ultimate strength. Uncertainty of axial compressive loads induced by hull girder bending is evaluated. Variability of still-water and vertical wave-induced bending moments are assessed. Factors that have significant impact on the panel reliability are investigated. Abstract: An assessment method is developed for the panel reliability of ship-shaped Floating, Production, Storage and Offloading units (FPSO). Not only axial compressive loads but also internal and external lateral pressures are taken into account in the reliability assessment. Beam-column buckling and flexural-torsional buckling are regarded as two primary failure modes of stiffened panels. Variability of corrosion wastage and material properties are accounted for in modelling the panel's time-dependent ultimate strength. Uncertainty of axial compressive loads induced by hull girder bending is evaluated based on probabilistic characteristics of still-water bending moment (SWBM) and vertical wave-induced bending moment (VWBM). A case study is performed to demonstrate this method and the effects of the lateral pressure, the return period of the extreme value of VWBM, the environmental severity factor, and the corrosion wastage on the panel reliability are investigated. Sensitivity measures for random variables are also carried out.